2001
DOI: 10.1007/s004210100522
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of explosive power and anaerobic capacity in humans

Abstract: There is a disparity in the information about the heritability of the response of muscle anaerobic metabolism to exercise and the use of explosive power, as well as a lack of information concerning the genetic determinants of this form of work, as measured using different specific physical tests. We applied a battery of some of the commonly employed procedures (Ergojump, Wingate, maximal accumulated oxygen deficit, excess post-exercise oxygen consumption, and delta lactate concentration) to a group of 32 Cauca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 25 publications
2
30
0
4
Order By: Relevance
“…To address this key question, which is a second step directed towards addressing adaptive hypotheses of physiological traits in insects, researchers should attempt to answer the more specific question: is standard metabolic rate heritable? Studies in vertebrates yielded mixed results (Calvo et al, 2002;Nespolo et al, 2003) but the fact that metabolic rate appear as important determinant of fitness in some species of cricket (Crnokrak and Roff, 2002) along with the results of this paper suggest that insect metabolism could be of selective importance.…”
Section: Metabolic Ratementioning
confidence: 78%
“…To address this key question, which is a second step directed towards addressing adaptive hypotheses of physiological traits in insects, researchers should attempt to answer the more specific question: is standard metabolic rate heritable? Studies in vertebrates yielded mixed results (Calvo et al, 2002;Nespolo et al, 2003) but the fact that metabolic rate appear as important determinant of fitness in some species of cricket (Crnokrak and Roff, 2002) along with the results of this paper suggest that insect metabolism could be of selective importance.…”
Section: Metabolic Ratementioning
confidence: 78%
“…Standard descriptive measures were used (mean and standard deviation). Differences between measures of monozygotic and dizygotic pairs of twins were assessed by the F value, calculated as the dizygotic variance divided by the monozygotic variance (Rodas et al, 1998;Calvo et al, 2002) after the normality assumption was verified with the Shapiro Wilk Test. Associations between variables were investigated with the Pearson Product-Moment coefficient.…”
Section: Statisticsmentioning
confidence: 99%
“…Later muscle biopsy studies on MZ and DZ twins identified that a major contributor to anaerobic performance, the relative percentage of fiber type, was 99.5% (men) and 93% (women) genetically determined [87]. Similarly, other factors that may affect anaerobic performance including muscular strength and power [28,50], peak blood lactate [82], and the anaerobic enzymes PFK and LDH [22] appear to have considerable genetic significance. Later work using different methodologies has suggested that many of the above factors that contribute to anaerobic performance are highly heritable including aerobic capacity (47%) [20], 10-and 90-s maximal work outputs (44-92%) [19,135], 30-s work capacity (86%) [83], muscular strength and mass [74], sprint running performance lasting less than 20 s [21], as well as the trainability of the anaerobic energy systems [19].…”
Section: Hereditymentioning
confidence: 99%